+0  
 
0
216
1
avatar

Sqaure root of l(l-5)=6

Guest Aug 6, 2017
 #1
avatar+7177 
+3

Is this your question?

 

\(\sqrt{l(l-5)}=6\)

                                                   Square both sides of the equation.

\(\sqrt{l(l-5)}^2=6^2 \\~\\ l(l-5)=36\)

                                                   Distribute the  l  to both terms in parenthesees.

\(l^2-5l=36\)

                                                   Subtract  36  from both sides of the equation.

\(l^2-5l-36=0\)

                                                   Use the quadratic formula to solve for  l  .

\(l=\frac{-(-5)\pm\sqrt{(-5)^2-4(1)(-36)}}{2(1)} \\~\\ l=\frac{5\pm\sqrt{25+144}}{2} \\~\\ l=\frac{5\pm13}{2} \\~\\ \begin{array} \ l=\frac{5+13}{2}\qquad &\text{or}&\qquad l=\frac{5-13}{2}\\~\\ l=9&\text{or}&\qquad l=-4 \end{array}\)

hectictar  Aug 7, 2017

15 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.